Pediatric non-COVID community-acquired pneumonia: Correlation of etiology, innate immune responses and the impact of feeding practices - Jasim, Rasha A.F.; Ewadh, Ruqaya Munther Jalil; Al-Hindy, Hayder Abdul-Amir Makki (Edelweiss Applied Science and Technology, 2024)
Community-acquired pneumonia (CAP) is a lower respiratory tract infection in a healthy child who has not recently been admitted to the hospital. Being the primary line of defense against bacterial and viral infections, the innate immune system is vital to protecting against CAP. The study aims to inspect the effects of feeding practices on the innate immune response in pediatric NCCAP, with particular attention paid to WBCs, CRP, TLR2, and TLR4.The study was a multi-center, cross-sectional enlisted 190 participants, separated into three groups based on the forms of feeding that the children engaged received: 80 were breastfed, 90 received artificial feeding, and 20 received mixed feeding. The following data were collected from every participant: demographic features, clinical parameters, and laboratory tests of TLR2, TLR4, CRP, WBCs, and identification of the microbial causation of pneumonia. Polymerase chain reaction tests were used to exclude patients with COVID-19 infection. Most of the immune parameters (WBC and the differential count) have means that are comparable between males and females. There are variations in the values of TLR4 with P- 0.028 and TLR2 with P- 0.025, between sexes. Breastfed infants show significantly lower TLR4 and TLR2 levels compared to artificially fed infants, while there were no significant differences are observed in CRP levels among the feeding groups. Feeding practices influence immune parameters, highlighting different profiles in breastfed babies. While presenting valuable insights, the conclusions warrant justification through larger clinical trials.